Pilot fatigue survey: A study of the mutual influence among fatigue factors in the "work" dimension - Sun Jun-Ya; Sun Rui-Shan (Frontiers Media S.A., 2023)
BackgroundFatigue risk management for pilots has received increasing attention. The existing fatigue management systems have detailed descriptions of the factors and the mutual influences among the factors that affect the dimension of "sleep", which is one of the most important causes of fatigue. However, the analysis of the influencing factors of the "work" dimension of fatigue causes has not been very detailed or accurate, especially the exploration of the mutual influence among many fatigue-influencing factors in the "work" dimension.ObjectiveThe purpose of this study was to explore the mutual influence among fatigue-influencing factors related to the "work" dimension in the analysis of pilot fatigue causes.MethodsThis study designed a questionnaire on the dimension of "work" in the causes of pilot fatigue and collected a total of 270 feedback data points from international flight pilots. Based on the questionnaires and data, descriptive statistical analysis, exploratory factor analysis and confirmatory factor analysis were performed to explore the influencing factors and their mutual influences on the "work" dimension of pilot fatigue.ResultsThere is a strong, mutual influence relationship among the fatigue causes of long-haul flight pilots - working status, working conditions and working schedules - in the dimension of "work". The workload only has a strong correlation with the working schedule, and the interaction relationships with the working status or working conditions are weak.ConclusionThis study analyses the mutual influence among the influencing factors of the "work" dimension of pilot fatigue, and we expect to provide empirical data for pilot fatigue risk management and to help improve fatigue risk management systems.